Base-resolution detection of N(4)-methylcytosine in genomic DNA using 4mC-Tet-assisted-bisulfite- sequencing - Yu, Miao (Nucleic Acids Res, 2015)
Restriction-modification (R-M) systems pose a major barrier to DNA transformation and genetic engineering of bacterial species. Systematic identification of DNA methylation in R-M systems, including N(6)-methyladenine (6mA), 5-methylcytosine (5mC) and N(4)-methylcytosine (4mC), will enable strategies to make these species genetically tractable. Although single-molecule, real time (SMRT) sequencing technology is capable of detecting 4mC directly for any bacterial species regardless of whether an assembled genome exists or not, it is not as scalable to profiling hundreds to thousands of samples compared with the commonly used next-generation sequencing technologies. Here, we present 4mC-Tet-assisted bisulfite-sequencing (4mC-TAB-seq), a next-generation sequencing method that rapidly and cost efficiently reveals the genome-wide locations of 4mC for bacterial species with an available assembled reference genome. In 4mC-TAB-seq, both cytosines and 5mCs are read out as thymines, whereas only 4mCs are read out as cytosines, revealing their specific positions throughout the genome. We applied 4mC-TAB-seq to study the methylation of a member of the hyperthermophilc genus, Caldicellulosiruptor, in which 4mC-related restriction is a major barrier to DNA transformation from other species. In combination with MethylC-seq, both 4mC- and 5mC-containing motifs are identified which can assist in rapid and efficient genetic engineering of these bacteria in the future.